Impact of linear thermal bridges on thermal transmittance of renovated apartment buildings - Ilomets, Simo; Kuusk, Kalle; Paap, Leena; Arumägi, Endrik; Kalamees, Targo (Journal of Civil Engineering and Management, 2017)
Renovation of old apartment buildings is a topic of current research interest throughout the Eastern Europe region where similar typology is derived from the period of 1960–1990. Thermal bridges, essential components of the transmission heat loss of a building, have to be properly evaluated in the energy audit during current state-of-the-art situation as well as in the comparison of renovation solutions. Resulting from field measurements and calculations, we propose linear thermal transmittances Ψ of thermal bridges for four types of apartment buildings: prefabricated concrete large panel element, brick, wood (log), and autoclaved aerated concrete. Our results show that thermal bridges contribute 23% of the total transmission heat loss of a building envelope before renovation. After renovation thermal bridges account for only 10% if windows are repositioned into additional external thermal insulation and balconies are rebuilt as best practice. Inversely, impact of the thermal bridges might be up to 34%, depending on the wall insulation thickness. We have also found that the relative percentage of thermal bridges after renovation increases and the negative impact of the thermal bridges of certain junctions cannot be compensated with thicker wall insulation. Results obtained in this paper are useful for energy audits.First published online: 13 Jun 2016